Stock Price Behaviour around the Announcement Date of Cash Dividend on the Indonesia Stock Exchange - Mujilan Mujilan (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study aims to explain the stock prices behavior around the announcement date of cash dividends. The study compares the stock prices a week before the cumulative date, cumulative date, record date, a week after the record date, and two weeks after the record date. The stock prices are also compared to the cash dividends nominals in 2017 and cash dividends in 2018. The researcher obtains the research data from LQ45 companies in 2018. The data is tested using the Wilcoxon Signed-Ranks Test. The results show that the date of announcement and recording of dividends do not have an impact on the increase in stock prices, but the result shows a decline in stock prices. The results of this study imply that the announcement of cash dividends does not trigger stock buying action around the announcement date for the companies who distribute cash dividends.